Fast‐Response Variable‐Stiffness Magnetic Catheters for Minimally Invasive Surgery - Yegor Piskarev; Yi Sun; Matteo Righi; Quentin Boehler; Christophe Chautems; Cedric Fischer; Bradley J. Nelson; Jun Shintake; Dario Floreano (Advanced Science, 2024)
Abstract In minimally invasive surgery, such as cardiac ablation, magnetically steered catheters made of variable‐stiffness materials can enable higher dexterity and higher force application to human tissue. However, the long transition time between soft and rigid states leads to a significant increase in procedure duration. Here, a fast‐response, multisegmented catheter is described for minimally invasive surgery made of variable‐stiffness thread (FRVST) that encapsulates a helical cooling channel. The rapid stiffness change in the FRVST, composed of a nontoxic shape memory polymer, is achieved by an active cooling system that pumps water through the helical channel. The FRVST displays a 66 times stiffness change and a 26 times transition enhancement compare with the noncooled version. The catheter allows for selective bending of each segment up to 127° in air and up to 76° in water under an 80 mT external magnetic field. The inner working channel can be used for cooling an ablation tip during a procedure and for information exchange via the deployment of wires or surgical tools.